KATIE: modelo de tecnologia assistiva aplicando visão computacional para auxiliar pessoas com deficiência visual na identificação de medicamentos - Steffenon, Jaqueline Dahmer (Universidade do Vale do Rio dos Sinos, 2020)
Assistive technology aims to promote the inclusion of people with disabilities in daily activities through the use of technological innovations. razil has approximately 1 million blind people, so it is essential to develop technologies to improve the lives of this population. From the objective of promoting the autonomy of these people, the theme of this work is reached: the expansion of access to information to those who are deprived of it due to blindness. Routine tasks, such as identifying a drug pack or reading the packaging of a food product, become challenges for those who live with this disability. Routine tasks, such as identifying a drug pack or reading the packaging of a food product, become challenges for those who live with this disability. Inspired by existing solution Be my eyes, this work emerges in order to develop a technological solution to the problem and make these totally independent mundane tasks of others. In this sense, the KATIE model is presented, in which the user can ask a question about the scenario in which he finds himself and have an answer in real time. The results obtained with tests in the identification of medicines and cash notes, show that the prototype was able to fulfill the estimated objective, performing the recognition of the question and image data and returning an adequate answer to the user
Keywords: Pessoas com deficiência visual; Visão Computacional; Reconhecimento de fala; Processamento de Linguagem Natural; Visually impaired people; Computer Vision; Speech Recognition; Natural Language Processing